Quality Education Management At Private Universities In Bangladesh: An Exploratory Study - Mohammad A. Ashraf, Mohammad A. Ashraf; Ibrahim, Yusnidah; Mohd. H. R. Joarder, Mohd. H. R. Joarder (Penerbit Universiti Sains Malaysia, 2009)
An exploratory survey was conducted to analyse the consumers’ (students’) evaluation of private higher education sectors in Bangladesh with particular reference to the quality as well as the cost of education. The sample was taken on a random basis from about ten private universities in the Dhaka metropolitan area. The respondents (students) were asked to evaluate the quality and the cost of education at private universities in Bangladesh. Respondents ranked the attributes according to a number of itemised sevenpoint scale ratings bounded at each end by one of two bipolar adjectives. The results of this study show that faculty credentials, the academic calendar, campus facilities, research facilities and cost of education are associated with quality education, and that the consumers feel most of the private universities in Bangladesh provide quality education at unreasonably higher costs.